Hybrid fast damping control strategy for doubly fed induction generators against power system inter-area oscillations - Xu, Yan (2018)
Here, a hybrid fast damping control strategy based on bang-bang modulation is proposed for doubly fed induction generators (DFIGs) against inter-area oscillations. Since the changes in active power modulation of DFIG may result in its interactive effect with torsional oscillations, this study relies on the modulation of DFIG reactive power to rapidly attenuate the system's critical oscillation mode. In order to overcome the buffeting of the bang-bang modulation, the proposed control strategy is designed as a hybrid scheme consisting of three operating modes which are switched based on the amplitude of the detected critical oscillation mode. The required lead phase for the proposed control strategy is determined using frequency domain analysis using detailed dynamic model of the DFIG. A comprehensive test is carried out by conducting simulation studies on a modified two-area system including an aggregated wind farm. It has been shown that the proposed strategy damps inter-area oscillations much quicker than the conventional continuous damping controller. Simulation results also showed that the control scheme is robust to the operation point variation and identification errors for practical application.